Gradual Covering Location Problem with Stochastic Radius - Mahdi Bashiri; Elaheh Chehrepak; Saeed Gomari (Innovative Methods in Logistics and Supply Chain Management: Current Issues and Emerging Practices. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 18, 2014)
In this paper, we consider the gradual covering problem when the coverage radius, is determined by a random variable with distinct distribution functions. In this model, it is assumed that the certain amount of coverage radius is not available and the potential coverage radius is used. Model will be solved using CPLEX method for different distribution functions. Then, the objective function values for the selected layout calculated by changing coverage radius between 100 randomly generated numbers with distinct distributions. The results are compared with the classical model of gradual covering. The results show that the proposed model will provide the desired results for a possible covering radius.
10419/209188; https://econpapers.repec.org/RePEc:zbw:hiclpr:19
Keywords: 650; covering radius; gradual covering; stochastic models; normal and uniform distributions